Mineral and trace metal supplement for use with synthetic diets based on comminuted chicken. Issue 12 (December 1978) - Thorn, J M; Aggett, P J; Delves, H T; Clayton, B E
Abstract : Earlier studies (Alexander et al., 1974; Lawson et al., 1977) suggested a suitable composition for a mineral and trace metal supplement for use with synthetic diets containing some natural food. Such a mixture has been evaluated in patients receiving a diet based on comminuted chicken and has been shown to be adequate. This conclusion was based on balance experiments measuring Zn, Cu, Mn, Fe, Ca, Mg, N, and P.